EP700 Pelvic exenteration for recurrent gynaecological cancer- outcome of patients referred but not operated on. (1st November 2019) - Bryan, S; Mahmoodi, I; Kolomainen, D; Barton, D
Abstract : Introduction/Background: The main goal of pelvic exenteration (PEx) for recurrent cancer is to achieve cure. This is most strongly associated with R0 resection, which is also associated with prolonged disease-free interval. Patients typically have been treated with radical surgery, and/or radiotherapy (RT) or chemo-RT. Not all patients referred for PEx will undergo surgery. We set out to establish why PEx was not performed and to determine the outcomes of these patients. Methodology: We retrospectively collected the data of all patients who were referred for consideration of pelvic exenteration between August 2004 and June 2018. The database was populated from MDT and surgical records. All cases were either recurrent cancer or persistent disease following prior RT/chemo-RT. Results: There were 90/202 referred during the study period who did not undergo PEx. The mean age at initial diagnosis was 51years. Over half (51%) of the patients had a diagnosis of cervical cancer. The reasons for not undergoing PEx were: 1. R0 would not be achieved (27%), 2. patient declining surgery (21%), 3. Metastatic disease (19%), 4. Extensive disease (14%), 5. Adverse patient co-morbidities (7%), 6. More suitable treatment available (6%), and 7. Procedure abandoned (2%). Of the 90 patients, 64 had died. The mean disease-free interval was 33.7 months, and the mean survival after decision made not for exenteration was 16.4 months. The majority of patients went on to have chemotherapy. Conclusion: Approximately 50% of patients referred for PEx for recurrent gynaecological cancer are not operated on. The most common reason being that R0 would not likely be achieved, although one fifth declined surgery. Mean survival after decision made not for exenteration was just over a year. Majority of patients went on to have palliative chemotherapy. As expected, those who had no further treatment died sooner than those who underwent other treatments. Disclosure: Nothing to disclose.